2003
DOI: 10.1046/j.0016-8025.2003.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐structural carbon compounds in temperate forest trees

Abstract: The current carbon supply status of temperate forest trees was assessed by analysing the seasonal variation of nonstructural carbohydrate (NSC) concentrations in leaves, branch wood and stem sapwood of 10 tree species (six deciduous broad-leafed, one deciduous conifer and three evergreen conifer trees) in a temperate forest that is approximately 100 years old. In addition, all woody tissue was analysed for lipids (acylglycerols). The major NSC fractions were starch, sucrose, glucose and fructose, with other ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
640
5
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 689 publications
(711 citation statements)
references
References 32 publications
54
640
5
12
Order By: Relevance
“…Chemical analyses of the 6136 leaf samples indicated extremely wide-ranging concentrations of NSC, from 16.5% to 84.5% of total leaf mass (Table 3). Parallel to the spectra, this NSC range approximately meets the range reported for live, fresh foliar material worldwide [1,5,9]. Based on this range of chemical values, the PLSR analyses indicated that NSC can be estimated at the leaf level from reflectance with high precision (mean R 2 = 0.73 ± 0.06) and accuracy (average %RMSE = 12.9%) ( Table 3).…”
Section: Leaf-level Performancementioning
confidence: 79%
“…Chemical analyses of the 6136 leaf samples indicated extremely wide-ranging concentrations of NSC, from 16.5% to 84.5% of total leaf mass (Table 3). Parallel to the spectra, this NSC range approximately meets the range reported for live, fresh foliar material worldwide [1,5,9]. Based on this range of chemical values, the PLSR analyses indicated that NSC can be estimated at the leaf level from reflectance with high precision (mean R 2 = 0.73 ± 0.06) and accuracy (average %RMSE = 12.9%) ( Table 3).…”
Section: Leaf-level Performancementioning
confidence: 79%
“…The higher gross WUE P as a consequence of precipitation could be explained by a few reasons. Firstly, by using the long-term water use effi ciency based on AB increment and not on CO 2 uptake and transpiration ratio, the relative carbon allocation to roots or AB can play important role (Höll, 1985;Lindroth et al, 1994;Dickmann et al, 2001;Hoch et al, 2003). During the period with reduced soil water availability, the assimilated carbohydrates are directed away from shoots and towards root growth.…”
Section: Discussionmentioning
confidence: 99%
“…Plant storage pools in the form of non-structural carbohydrates are known to play an important role in regulating allocation to structural pools, and they may make up a significant portion of total biomass (e.g., Hoch et al, 2003). Simple models that account for non-structural carbohydrates better compare with observed 14 C and stem growth, indicating the importance of the pools over seasonal to decadal timescales .…”
Section: Assessment Of Model Performance In Treatment Periodmentioning
confidence: 99%